Pengaruh Kepemimpinan Transformasional terhadap Organizational Citizenship Behavior Karyawan RS X Kota Padang - Dea Fenny Kirana Putri; Fidia Oktarisa (ARZUSIN, 2026)
Although transformational leadership style is often regarded as a factor that can encourage employees’ Organizational Citizenship Behavior (OCB), this relationship does not always show a positive direction, particularly in the healthcare sector, which requires intensive cooperation and high service quality. This study aimed to determine the effect of transformational leadership style on OCB among employees at Hospital X, Padang City. This study employed a quantitative approach with a simple linear regression design. The study population comprised all employees of Hospital X, Padang City, with a sample of 144 employees selected through simple random sampling. Data were collected using Likert scales based on aspects of transformational leadership and OCB, and were then analyzed statistically to examine the relationship between variables. The results showed that transformational leadership style had a negative and significant effect on OCB, with a regression coefficient of -0.149 and a significance value of 0.019 (p < 0.05). These findings indicate that an increase in transformational leadership style is not always followed by an increase in OCB, suggesting the possibility that other factors, such as organizational culture, workload, or job satisfaction, play a greater role in influencing OCB. Thus, this study emphasizes that the effectiveness of transformational leadership in encouraging extra-role behavior needs to be understood contextually within the hospital environment and contributes to the development of organizational behavior studies in the healthcare service sector.